2007
DOI: 10.1021/jf0623079
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Malt Quality Parameters and Beer Flavor Stability:  Multivariate Analysis

Abstract: Malt is known to have an impact on beer flavor stability mainly due to the presence of antioxidants. In this study, five barley varieties were malted at industrial and micro scale, and quality parameters of the resulting malts were measured (diastatic power, friability, beta-glucan content, antiradical power, reducing power, lipoxygenase activity, and nonenal potential) and correlated with the sensory data obtained for the corresponding fresh and forced aged beers. A statistical strategy using multiple linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 17 publications
2
40
1
1
Order By: Relevance
“…The role of phenolic compounds in relation to the colour, taste, and stability of beer is well known. Beer rich in phenolic antioxidants shows higher quality, more stable sensory properties such as flavor and aroma, foam stability, and longer shelf life (Drost et al 1990;Guido et al 2007;McMurrough et al 1996;Woffenden et al 2001).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The role of phenolic compounds in relation to the colour, taste, and stability of beer is well known. Beer rich in phenolic antioxidants shows higher quality, more stable sensory properties such as flavor and aroma, foam stability, and longer shelf life (Drost et al 1990;Guido et al 2007;McMurrough et al 1996;Woffenden et al 2001).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The malts used for the preparation of the six commercial lager beers, were evaluated for parameters considered to be significant in terms of their influence on the flavour stability of beer 28 . These potentially relevant quality parameters of malt are lipoxygenase activity, trihydroxy fatty acid content, and TB-index (see Table II).…”
Section: Evaluation Of Maltmentioning
confidence: 99%
“…The effect of polyphenols on the antioxidant properties of wort and beer is unclear. There is evidence that polyphenols have significant antioxidative properties 11,28,40,41,46,49,60 . However, Andersen et al 2,3 reported that phenolic compounds are neither antioxidants nor pro-oxidants.…”
Section: Introductionmentioning
confidence: 99%